2020
DOI: 10.1002/jor.24777
|View full text |Cite
|
Sign up to set email alerts
|

Bright ultrashort echo time SWIFT MRI signal at the osteochondral junction is not located in the calcified cartilage

Abstract: In this study, we aimed to precisely localize the hyperintense signal that is generated at the osteochondral junction when using ultrashort echo time magnetic resonance imaging (MRI) and to investigate the osteochondral junction using sweep imaging with Fourier transformation (SWIFT) MRI. Furthermore, we seek to evaluate what compositional properties of the osteochondral junction are the sources of this signal. In the study, we obtained eight samples from a tibial plateau dissected from a 68‐year‐old male dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…This can be caused by signal contribution from the deep layer, which also has a short T 1 , short T 2 blurring, and partial volume effect (using a relatively thick slice of 2 mm in this study). A most recent study also demonstrated that the bight signals were mainly located at the deep layer cartilage [30]. In general, the qualitative method is more likely to be of clinical utility, given that assessment is rapid and intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…This can be caused by signal contribution from the deep layer, which also has a short T 1 , short T 2 blurring, and partial volume effect (using a relatively thick slice of 2 mm in this study). A most recent study also demonstrated that the bight signals were mainly located at the deep layer cartilage [30]. In general, the qualitative method is more likely to be of clinical utility, given that assessment is rapid and intuitive.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the IR-FS-ZTE sequence's TE of 12 µs should be able to directly detect signals from these tissue regions. However, a recent study by Nykanen et al found that the bright signal line seen in UTE sweep imaging with Fourier transformation (SWIFT) imaging of cartilage samples resided within the deep radial noncalcified cartilage (44). This is likely due to the low proton densities of the calcified cartilage and subchondral bone, as well as their extremely short T 2 *s, which together result in a very low signal intensity in SWIFT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The SNR in the subchondral plate with SWIFT (0.91) was more than four times higher than with conventional FSE (0.12) and GRE (0.19) MR images 76 . The same group carefully coregistered the SWIFT MRI, μCT, and histology images for the OCJ samples 65 . They found that the bright SWIFT MRI signal at the OCJ region is not located in the calcified cartilage but in the deep layers of the radial zone in cartilage.…”
Section: Swift Imaging Of the Ocjmentioning
confidence: 99%